السندات الرسمية والعرفية وحجيتها في الإثبات في القانون المدني الجزائري - أنيس صحراوي (My University, 2021)
Summary of note: Finally, as a complete summary of our topic, in our research we touched upon in our first chapter both what are official bonds and what are customary bonds. We found that official bonds have a semi-uniform definition in most comparative legislation which is the same definition as Algerian law, relying on the terms of the official bond therein, We have addressed these conditions: the official paper must be issued by an official, public officer or a person in charge of a public service. and provided that its liberation is within the limits of its authority and competence, taking into account the forms and rules established by law. and the failure of these conditions may result in the nullity of the official bond in absolute nullity or may result in its conversion into a customary bond. With regard to customary bonds, we found that Algerian legislation and jurisprudence depended in their definition on their characteristic of lack of formality and the non-requirement of certain procedures for their liberalization. As defined earlier, they are less complex and easier on the procedural side of their predecessor, However, this has not prevented the existence of two important conditions for its validity, namely, that it must be in writing without requiring any form of any kind, as well as that it must be available for signature. In chapter II of our research, we studied the authenticity of official and customary bonds following the same division: As to the authenticity of official bonds, we found that they had authenticity for people. ", whether they are parties to the formal contract or even for others, In both cases, this type of bond has absolute validity on the presumption that it is legally valid and may only be challenged by falsification in the case of statements made by the official or public officer within the limits of his authority and functions and in his presence. In the case of data transmitted by the parties or outside the limits of the party's mission, the authenticity of the data is reduced in this case and can be refuted and proved to be reversed; We also touched upon the authenticity of the official bond photographs, which found that the asset had absolute authenticity and could only be challenged by forgery. However, its authenticity is weaker whenever the image is far from the original. In the authenticity of customary bonds, we found that they were in two types. The validity of bonds prepared for proof in Algerian law went through two stages, before the promulgation of the Documentation Act of 1971, and after the promulgation of the 1971 law. We also studied customary bonds not prepared for proof, namely letters and telegrams, commercial and home books and indication. ..................... ملخص المذكرة : وفي الأخير وكملخص كامل لموضوعنا فإننا في بحثنا هذا قد تطرقنا في فصلنا الأول إلى ماهية كل من السندات الرسمية وماهية السندات العرفية. فوجدنا أن للسندات الرسمية تعريف شبه موحد في معظم التشريعات المقارنة، وهو نفس التعريف الذي انتهجه القانون الجزائري معتمدا على شروط السند الرسمي في ذلك، وقد تطرقنا إلى هذه الشروط والتي تمثلت في وجوب صدور الورقة الرسمية من موظف أو ضابط عمومي أو شخص مكلف بخدمة عامة، وبشرط أن يكون تحريرها في حدود سلطته واختصاصه، مع مراعاة الأشكال والقواعد التي قررها القانون لذلك، وتخلف هذه الشروط قد يؤدي إلى بطلان السند الرسمي بطلان مطلق أو قد يؤدي إلى تحوله إلى سند عرفي. وبالنسبة للسندات العرفية فقد وجدنا أن التشريع الجزائري والفقه قد اعتمد في تعريفها على ذكر خصائصها المتمثلة في انعدام الرسمية وعدم اشتراط إجراءات معينة لتحريرها، وحسب التعريف السابق فهي أقل تعقيدا وأسهل في الجانب الإجرائي من سابقتها، إلا أن هذا لم يمنع من وجود شرطين مهمين لصحتها ألا وهما وجوب أن تكون مكتوبة بدون اشتراط أي شكلية من أي نوع كان، بالإضافة إلى وجوب توفرها على التوقيع. في الفصل الثاني من بحثنا قمنا بدراسة حجية السندات الرسمية والعرفية بإتباع التقسيم ذاته: حيث أنه بالنسبة لحجية السندات الرسمية وجدنا أنها تملك حجية للأشخاص، سواء كانوا أطرافا في العقد الرسمي أو حتى بالنسبة للغير، وفي كلا الحالتين تكون لهذا النوع من السندات حجية مطلقة بافتراض صحته قانونا ولا يجوز الطعن فيه إلا بالتزوير في حالة البيانات التي قام بتحريرها الموظف أو الضابط العمومي في حدود سلطته ومهامه وتمت بحضوره، أما في حالة البيانات تم نقلها له من قبل الأطراف أو كانت خارجة عن حدود مهمته فإن حجيتها تقل في هذه الحالة ويمكن دحضها وإثبات عكسها، وقمنا كذلك بالتطرق إلى حجية صور السند الرسمي والتي وجدنا بأن الأصل يتمتع بحجية مطلقة ولا يمكن الطعن فيه إلا بالتزوير، إلا أن حجيته تكون أضعف كلما كانت الصورة بعيدة عن الأصل. وفي حجية السندات العرفية وجدنا بأنها تكون في نوعان، فحجية السندات المعدة للإثبات في القانون الجزائري مرت بمرحلتين، قبل صدور قانون التوثيق لسنة 1971 ، ومرحلة ما بعد صدور قانون 1971 كما درسنا السندات العرفية الغير معدة للإثبات والتي تتمثل في الرسائل والبرقيات، والدفاتر التجارية والمنزلية والتأشير على السند. ................. Résumé de la note : Enfin, comme résumé complet de notre sujet, dans notre recherche, nous avons abordé dans notre premier chapitre à la fois ce que sont les obligations officielles et ce que sont les obligations coutumières. Nous avons constaté que les obligations officielles ont une définition semi-uniforme dans la plupart des législations comparatives qui est la même définition que la loi algérienne, en s’appuyant sur les termes de l’obligation officielle, Nous avons examiné ces conditions : le papier officiel doit être émis par un fonctionnaire, fonctionnaire public ou personne responsable d’un service public. et à condition que sa libération soit dans les limites de son autorité et de sa compétence, compte tenu des formes et des règles établies par la loi. et le non-respect de ces conditions peut entraîner la nullité du cautionnement officiel en nullité absolue ou peut entraîner sa conversion en un cautionnement coutumier. En ce qui concerne les obligations coutumières, nous avons constaté que la législation et la jurisprudence algériennes dépendaient dans leur définition de leur caractéristique d’absence de formalité et du non respect de certaines procédures